A novel wide-band dual function fiber amplifier - Hamida, Belal Ahmed; Khan, Sheroz; Ahmed Wathik, Naji; Al Khateeb, Wajdi Fawzi Mohammed; Harun, Sulaiman Wadi; Ahmad, Harith (Academic Journal, 2011)
The design of a novel wideband Dual-function Erbium-doped fiber amplifier (EDFA) with chirped fiber Bragg grating (CFBG) configured in two-stage double pass amplification scheme is demonstrated in this paper. The proposed architecture is designed to increase amplification bandwidth. The purpose of utilizing the CFBG is to reflect the amplified signal back to the Erbium-doped fiber and to compensate for the fiber dispersion. One of the most attractive features of this amplifier is the integration of both attenuation and dispersion compensation in a single black box. In this work, high gain and low noise figure (NF) for a long haul optical-fiber-communication system (OFCS) are considered as a main design objectives. Therefore, the effects of pump power, signal power, and wavelength on the gain and noise figure are analyzed from the numerical simulation of EDFA using rate equations model. The new proposed configuration is demonstrated using simulation and numerical modeling, and both results match with small differences. The configuration at low single power of -30 dBm is able to achieve gain up to 32.64 dB and noise figure of less than 5 dB